2022
DOI: 10.1021/acsanm.2c00802
|View full text |Cite
|
Sign up to set email alerts
|

Ag–Ga Bimetallic Nanostructures Ultrasonically Prepared from Silver–Liquid Gallium Core–Shell Systems Engineered for Catalytic Applications

Abstract: Silver (Ag) nanoalloys play significant roles in several industrial applications. While still many sustainable frameworks can be explored for the synthesis and functional incorporations, the control of phase and structure at the nanoscale still is a major challenge for their practical implementation. In this study, liquid-phase gallium (Ga(L)) nano-/microspheres were utilized for this purpose, investigating their function as reaction media and metallic alloying elements for the development of one-dimensional (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 73 publications
2
14
1
Order By: Relevance
“…The main factor for a sustainable CO 2 catalysis process relies on the generation of a cyclic path where the Ga(0) ↔ Ga + reaction occurs continuously in the system. Therefore, reversible conversion of Ga to Ga + should be guaranteed for continued CO 2 conversion, like what has been recently developed in a Ga microparticle system anchored with Ag 0.72 Ga 0.28 nanorods . In the present study, piezoelectric crystalline Se-rich nanodomains were grown on the Ga-In NP surface.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The main factor for a sustainable CO 2 catalysis process relies on the generation of a cyclic path where the Ga(0) ↔ Ga + reaction occurs continuously in the system. Therefore, reversible conversion of Ga to Ga + should be guaranteed for continued CO 2 conversion, like what has been recently developed in a Ga microparticle system anchored with Ag 0.72 Ga 0.28 nanorods . In the present study, piezoelectric crystalline Se-rich nanodomains were grown on the Ga-In NP surface.…”
Section: Resultsmentioning
confidence: 76%
“…Therefore, reversible conversion of Ga to Ga + should be guaranteed for continued CO 2 conversion, like what has been recently developed in a Ga microparticle system anchored with Ag 0.72 Ga 0.28 nanorods. 39 In the present study, piezoelectric crystalline Se-rich nanodomains were grown on the Ga-In NP surface. The ferroelectricity/piezoelectricity properties of elemental and crystalline Se at room temperature were reported recently, where a strong in-plane piezoelectric coefficient of 30 pm/V was recorded for a t-Se single crystal.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…It was reported that glutaric acid contains some elements, such as O, S, N, H, etc., that could form hydrogen bonds, covalent bonds, dipolar bonds, or ionic bonds with organic lubricants on the Ag surface and can improve the electrical conductivity and mechanical properties of the ECAs. In addition, it can be used to remove the surface oxide layer of liquid metal based inks, (e.g., gallium and gallium-based alloys), which greatly affects the interfacial properties of the liquid metal, such as adhesion, wettability, and rheological behavior of liquid metals . However, there are few reports on the related reaction mechanism of adding short-chain dibasic acid into the ECAs for improving the electrical and mechanical properties of the ECAs.…”
Section: Introductionmentioning
confidence: 99%
“…Low-meting-point post-transition metal-based liquid alloys, also known as liquid metals (LMs), are a burgeoning subject of studies due to their unique interfacial characteristics. 1−4 The interfaces of LMs are atomically smooth, chemically active, and stimulus-responsive, enabling a range of applications from materials synthesis 5 and thermal management 6−8 to catalysis 9−11 and sensing. 12−14 LMs are highly fusible alloys that can dissolve various metals.…”
Section: Introductionmentioning
confidence: 99%
“…Low-meting-point post-transition metal-based liquid alloys, also known as liquid metals (LMs), are a burgeoning subject of studies due to their unique interfacial characteristics. The interfaces of LMs are atomically smooth, chemically active, and stimulus-responsive, enabling a range of applications from materials synthesis and thermal management to catalysis and sensing. LMs are highly fusible alloys that can dissolve various metals. ,, The stratified surface of LMs in such alloys can undergo phase separation by oxidation and simultaneous templating onto the surface of the LM. Subsequently, the oxide at the interface can be harvested in a procedure that is generally referred to as “LM-assisted interfacial synthesis of two-dimensional oxides”. Additionally, by inducing physical perturbation at the LM interfaces, phase separation of solute metals, in their zero-valent form, can be achieved.…”
Section: Introductionmentioning
confidence: 99%